Biomonitoring for Improving Alcohol Consumption Surveys. - Greenfield, Thomas K.; Bond, Jason; Kerr, William C. (Alcohol Research: Current Reviews, 2014)
To assess alcohol consumption levels in large populations, researchers often rely on self-report measures. However, these approaches are associated with several limitations, particularly underreporting. Use of noninvasive biomonitoring approaches may help validate self-report alcohol consumption measurements and thus improve their accuracy. Two such devices currently are available, the WrisTAS™ and SCRAM™ devices, both of which measure alcohol vapors emitted through the skin after alcohol consumption. Several studies assessing the utility of the WrisTAS™ bracelet in determining alcohol consumption levels noted that it was associated with relatively high failure rates. The SCRAM™ is an ankle bracelet intended for court-ordered alcohol monitoring. In studies, its sensitivity exceeded that of the WrisTAS™ and increased with increasing blood alcohol concentrations. Although early studies also identified some equipment concerns with the SCRAM™, studies of its ability to detect moderate and heavy drinking recently have yielded good results. Biomonitoring devices already are valuable tools and with further improvements may become even more useful in both research and practical applications.